Economic stability in the GCC countries: A comparative study of the Kingdom of Bahrain and Sultanate of Oman - Babu, Manju Rajan; Taqi, Mohammad; Salari, Emma (Edelweiss Applied Science and Technology, 2025)
The present study focuses on economic stability in Gulf Cooperation Council (GCC) countries with special emphasis on the economy of Kingdom of Bahrain and Sultanate of Oman. This study is an attempt to examine Gross Domestic Product (GDP), per capita, unemployment, inflation, and interest rates in the Kingdom of Bahrain and Sultanate of Oman. The fluctuation in oil and gas prices affects the growth and development of economies the Gulf Cooperation Council to maintain stability and continuous growth. The present research investigates the major economic indicators like GDP growth, inflation rates, and unemployment rates to assess the resilience of the economies of the Kingdom of Bahrain and the Sultanate of Oman. It also examines the effects of diversification initiatives on the long-term economic stability of Bahrain and Oman, including Vision 2030 and investments in non-oil sectors. By examining both historical trends and current policy frameworks, it provides insights into the strategies that Bahrain and Oman should employ to reduce risks and enhance economic resilience in an increasingly unpredictable global economy. The results emphasize the importance of strategic planning and regional collaboration in promoting long-term economic growth and stability in the Kingdom of Bahrain and the Sultanate of Oman.